SPARC aberrant methylation in idiopathic pulmonary fibrosis: an explorative study - Fabrizio, Federico Pio; Sparaneo, Angelo; Centra, Flavia; Delli Muti, Francesco; Parente, Paola; Copetti, Massimiliano; Delcuratolo, Marco Donatello; Rossi, Antonio; Gili, Elisa; Rossi, Giulio; Graziano, Paolo; Muscarella, Lucia Anna (Frontiers in Cell and Developmental Biology, 2025)
IntroductionIdiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease (ILD) characterized by progressive accumulation of extracellular matrix in the lung and dysregulated activation of specific signaling pathways. Recent advances in the understanding of the biological bases of IPF identified the silencing of secreted protein acidic and rich in cysteine (SPARC) as a key modulator in the pathogenesis of IPF, although the mechanisms underlying the SPARC aberrant modulation remain to be fully elucidated.MethodsHere we investigated the aberrant methylation at the promoter gene region as a possible mechanism of SPARC deregulation in IPF. Formalin-fixed paraffin-embedded (FFPE) tissues from a cohort of 44 patients with IPF and from a control-group of 23 non-idiopathic pulmonary fibrosis (NIPF) were analyzed. DNA methylation analysis at the SPARC promoter region was assessed by quantitative methylation-specific PCR analysis (QMSP) and a total of 11 CpGs located in the gene promoter island were evaluated.ResultsMethylation levels were found to be significantly higher (p < 0.004, Mann-Whitney test) in 44 IPF samples (methylated using the optimal cut-off 20/44, 45%) compared to NIPF surgical biopsies (methylated using the optimal cut-off 3/23, 13%). At the in vitro level, we observed an inverse correlation between SPARC mRNA levels and hypermethylation under 5-Aza-2′-deoxycytidine (5-Aza-CdR) treatment when a primary fibrotic cell line was treated, whereas any variations were observed treating non-fibrotic cells.DiscussionOur explorative study suggests that promoter methylation of the SPARC gene is linked to IPF but not to NIPF, and could represent a potential molecular marker of disease, thus warranting further investigations on larger cohorts.